Mg in aragonitic bivalve shells: seasonal variations and mode of incorporation in Arctica islandica - Foster, L; Finch, Adrian Anthony; Allison, Nicola; Andersson, c; Clarke, LJ (Chemical Geology, 2008)
The potential of Mg in Arctica islandica as a climate proxy is explored through analysis of live-collected shells from Irvine Bay, NW Scotland. Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA-ICP-MS) analysis of the right hand valve from two specimens indicates that seasonal Mg/Ca variations do not correlate with seawater temperature. The highest Mg/Ca typically occurs at the annual growth checks in -November-February Mg/Ca variations between growth checks are significant in one specimen but usually not significant in the other. Mg/Ca measurements taken laterally across the band (i.e. perpendicular to direction of the growth) to determine heterogeneity of the aragonite deposited at the same time indicates that Mg/Ca concentration decreases with increasing distance from the periostracum in both shells. X-ray Absorption Near Edge Spectroscopy (XANES) indicates that Mg is not substituted into aragonite but is hosted by a disordered phase e.g. organic components or nanoparticles of an inorganic phase. Shell Mg/Ca variations may reflect changes in the concentration or composition of the disorded phase, as well as changes in the composition of the extrapallial fluid used for calcification. Such changes could reflect the relative transportation rates of Mg and Ca to the calcification site. (C) 2008 Elsevier B.V. All rights reserved.